An analysis of the items of nursing competency in oral feeding assistance for hospitalized hemiplegic patients in China: a qualitative study - Chen, Huifang; Nakatani, Hisae; Kanefuji, Akiko; Yang, Hongxia; Zhao, Haiwei; Rahman, Md Moshiur (International Journal Of Community Medicine And Public Health, 2019)
Background: Patients with hemiplegia often suffer from malnutrition and security threat due to disabilities and inadequate supports. This study aims to explore nursing perceptions regarding problems, necessary nursing supports, and nursing competencies required for the provision of oral feeding assistance to hospitalized hemiplegic patients. Methods: A qualitative study was conducted in Taian City, China in 2016. A purposive sampling method was used, and data were gathered using semi-structured interviews. Totally, 5 faculty members and 10 ward nurses in China were interviewed. In relation to the nursing status regarding oral feeding assistance in the case of hemiplegic patients, background and improvement measures in nursing practice were assessed. Data were analyzed using the content analysis method. Results: Four problems in providing oral feeding assistance to hemiplegic patients were identified: 1) insufficient cognition of nursing roles, 2) insufficient consideration of psychological aspects of the patients, 3) lack of related theoretical and practical education, 4) lack of nutritional support during hospitalization. Twenty-five items of nursing competencies, the knowledge and skills required for oral feeding assistance to hospitalized hemiplegic patients were identified. Conclusions: The nursing competency identified by this study can provide evidence for reviewing the related nursing practice and continuous education in China.